Synthesis of Dibenzothiophenium Salts and Observations in Radiofluorination - Zhang, Juntian; Zhang, Wei; Hoye, Adam T.; Lim, Nathaniel C.; Xiong, Hui (Synlett, 2025)
We demonstrate an alternative synthesis of dibenzothiophenium (DBT) salts through a three-step Pd-catalyzed arylation, oxidation, and cyclization sequence. This approach is operationally straightforward and compatible with a variety of common functional groups. We observed that radiofluorination of a set of related DBT salt precursors gave higher radiochemical incorporation (RCI) with substrates bearing ortho-substituents to the DBT leaving group, suggestive of an ortho-effect.
Keywords: dibenzothiophenium salts; ortho-effect; radiofluorination